Millimeter-wave phased-array for broadband wireless applications - Ellis, G. A.; Al-Majeed, S. (Nazarbayev University, 2013)
Typical scenarios for application of this technology are shopping malls, airports, convention centers, and dense urban settings and situations where a large number of users transmit and receive large amounts of data. This includes real-time video and cloud computing. For non line of sight situations having the presence of multipath, each antenna of a Smart or MIMO (multiple-input, multiple-output) antenna, e.g. upcoming 5G system, could be a phased array to increase capacity.
Keywords: first research week; broadband wireless communications; higher security